Effect of type of sport, weekly physical exertion and body mass index on values of bone turnover markers in elite female athletes - Nenad Ponorac; Tanja Šobot; Nela Rašeta (Биомедицинска истраживања, 2018)
Introduction: The aim of the study was to determine the level of bone turnover markers (serum middle fragment of osteocalcin and b-CrossLaps) in young female athletes involved in different sports, as well as to determine the relation between bone turnover markers (BMT) and type of sports activity, weekly physical exertion and body mass index. Methods: Out of a total of 111 female participants, 78 of them were elite athletes while the control group consisted of 33 female students of the faculty of medicine, of a similar age. Athletes with any kind of menstrual irregularity (N=18) were excluded from the study. Therefore, the sample was comprised of 27 basketball and handball players, 11 middleand long-distance runners and 22 dancers. Results: Athletes belonging to ball game group had significantly greater body mass index and sport experience compared to the other two groups, while the dancers had the lowest weekly physical exertion. There was a statistically significant difference in serum level of osteocalcin bone markers (49.55 ± 16.83 vs. 36.13 ± 7.26; p = 0.001) and b-CrossLaps (0.75 ± 0.25 vs. 0.53 ± 0.14; p = 0.001) between female athletes and the control group respondents. Ball game players had a greater osteogenic effect compared to runners and dancers (p < 0.05). Furthermore, the results revealed significant connection between weekly physical exertion and body mass index on the one hand and BMT level on the other hand. Conclusion: Chronic physical activity exerts an osteogenic effect, which is made evident by the concentration of serum level of osteocalcin significantly connected with weekly physical exertion.
Keywords: bone turnover markers; osteocalcin; β-CrossLaps; sport